Bridging the Surgical Gap: Evaluating Access to Safe, Timely and Affordable Surgical Care in Low- and Middle-Income Countries (LMICs) - Wandala, Abali; Ahmed Fadlelseed, Anas Fadlelseed; Himayat, Maria; Abdelwahab Abdalla, Abdalla Osman; Ahmed Fadlelseed, Amgad Fadlelseed; Jamshaid Ur Rehman (Indus Journal of Bioscience Research, 2025)
The quasi-experimental research assesses the impact of early, inexpensive, and safe surgical care on post-operative outcomes for low- and middle-income country (LMIC) patients. The study compares honest care with an improved intervention planned to maximize access and reduce delay in treatment. Quasi-experimental design was employed to select a sample of 240 patients operated from LMIC hospitals, on whom recovery time, surgical complications, and other associated variables were recorded. Statistical tests including independent samples t-test, chi-square test, and binary logistic regression were applied to examine group differences and predictors of surgical outcomes after controlling for confounders. Evidence shows that early surgery improves recovery time significantly, minimizes post-operative complications, and predicts better patient outcomes. The evidence recognizes broader gaps in surgical access and calls for training of the workforce, arrangement, and policy improvements to close surgical differences in LMICs. This article presents vital evidence in support of targeted interventions in enhancing surgical care quality and accessibility in low-resource environments. This research highlights the importance of safe, timely surgical care in improving outcomes in low- and middle-income countries. Quasi-experimental findings show enhanced recovery and fewer complications with improved care. Early intervention independently predicts better outcomes, emphasizing efficiency and risk stratification. The study supports broader health system reform through NSOAPs, advocating workforce development, decentralization, and innovative models like mobile units and telemedicine. These strategies aim to expand surgical access, especially in underserved rural areas, promoting equity and better health for all.